Numerical investigation of characteristics of phased antenna arrays, based on printed quasi-Yagi radiating elements (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2013)
Abstract. Paper presents numerical investigation of radiation and matching characteristics of a printed quasi-Yagi antenna and 11x11 2D  phased array, based on quasi-Yagi radiating elements. Results were obtained by finite-difference time domain method. The investigation of characteristics basic radiating element of phased array. Calculated matching characteristics and radiation pattern of quasi-Yagi antenna. Also shown mutual coupling between radiating elements by using 1D subarray, which has 9 elements. The investigation of characteristics of phased antenna array, based on printed quasi-Yagi radiating elements. Calculated radiating characteristics of phased antenna array. Determined the possible range scanning of phased array. Investigated applicability of quasi-Yagi radiating elements in building phased antenna arrays. Conclusions. Results of investigation have practical direction in solving the problems of constructing large phased antenna arrays.